2018
DOI: 10.1038/s41598-018-26242-6
|View full text |Cite
|
Sign up to set email alerts
|

Commercially Available Natural Benzyl Esters and Their Synthetic Analogs Exhibit Different Toxicities against Insect Pests

Abstract: Benzyl methyl ester, also known as methyl benzoate (MB), is a volatile organic compound that exists naturally as a floral fragrance in many plants. Our behavioral bioassays show that MB and some of its naturally occurring and synthetic analogs kill insects at different life stages. Compared to commercial pesticides containing pyriproxyfen and acetamiprid, MB and some analogs are 1.3 to 3.4 times more toxic to gypsy moth larvae and brown marmorated stinkbug nymphs. The arthropod repellent DEET is also a benzyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Decreases of tryptophan, phenylalanine, and beta-tyrosine levels and those of several phenolic and indole-related compounds derived from them were registered in the susceptible inbred after 9 days of feeding. On the contrary, indole-derived DIMBOA glucoside (antibiotic against S. nonagrioides larvae) and indole-acrylate (plant hormone) or the phenylpropanoids methyl-4-methoxy-3-nitrobenzoate (probable insecticide), 4-hydroxy-6-methylcoumarin (biocide), sinapaldehyde (intermediate in lignin formation), or o-hydroxyhippurate (insect antifeedant, also known as salicylurate; Ortego et al, 1998;Stuart et al, 2000;Cutler et al, 2002;Feng et al, 2018) were upregulated in the resistant inbred by MCB feeding. We also observed a decrease of several nitrogen-containing compounds in the susceptible inbred, while those compounds increased in the resistant inbred after 9 days of feeding; however, levels were still higher in the susceptible inbred.…”
Section: Resultsmentioning
confidence: 99%
“…Decreases of tryptophan, phenylalanine, and beta-tyrosine levels and those of several phenolic and indole-related compounds derived from them were registered in the susceptible inbred after 9 days of feeding. On the contrary, indole-derived DIMBOA glucoside (antibiotic against S. nonagrioides larvae) and indole-acrylate (plant hormone) or the phenylpropanoids methyl-4-methoxy-3-nitrobenzoate (probable insecticide), 4-hydroxy-6-methylcoumarin (biocide), sinapaldehyde (intermediate in lignin formation), or o-hydroxyhippurate (insect antifeedant, also known as salicylurate; Ortego et al, 1998;Stuart et al, 2000;Cutler et al, 2002;Feng et al, 2018) were upregulated in the resistant inbred by MCB feeding. We also observed a decrease of several nitrogen-containing compounds in the susceptible inbred, while those compounds increased in the resistant inbred after 9 days of feeding; however, levels were still higher in the susceptible inbred.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison, blueberries pretreated with 1% or 5% MB were associated with 100% mortality of Drosophila suzukii (Matsumura) (Diptera: Drosophilidae) 48 h after exposure in small‐fruit agroecosystems . Feng et al . found that MB and certain related analogs were 1.3–3.4 times more toxic to larvae of Lymantria dispar (L.) (Lepidoptera: Erebidae) and nymphs of Halyomorpha halys (Stål) (Hemiptera: Pentatomidae) than commercial pesticides containing pyriproxyfen and acetamiprid.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, MB isolated from fermented apple juice has been reported to have insecticidal properties against several insect pests . Besides MB, nine other naturally occurring benzoate derivatives—ethyl benzoate (EB), n ‐propyl benzoate (nPrB), methyl 2‐methylbenzoate (M2 MB), methyl 2‐methoxybenzoate (M2MOB), iso‐butyl benzoate (iBB), n‐butyl benzoate (nBB), n‐pentyl benzoate (n‐PeB), n‐hexyl benzoate (nHB), and BB—have been assessed for contact toxicity against certain insect pests . However, to the best of our knowledge, there has been no report on the acaricidal activity of benzoate derivatives, particularly against phytophagous mite pests of plants.…”
Section: Introductionmentioning
confidence: 99%
“…Natural products can often provide a more environmentally-friendly approach to managing insect pests and plant diseases [42,43]. MB, which is a naturally occurring compound found in many plants, exhibits potent insecticidal activity against a variety of insect pests [18,[21][22][23][24]44]. Therefore, MB could provide an alternative to synthetic insecticides for agricultural control of cotton aphids in the near future.…”
Section: Discussionmentioning
confidence: 99%